2004
DOI: 10.1161/01.atv.0000122362.44628.09
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Mouse Angiopathy Is Linked to Progressive Sympathetic Receptor Deletion Coupled to an Enhanced Caveolin-1 Expression

Abstract: Objective-Clinical studies have demonstrated that hyperglycaemia represents a major risk factor in the development of the endothelial impairment in diabetes, which is the first step in vascular dysfunction. Using non-obese diabetic mice, we have evaluated the role of the adrenergic system and eNOS on progression of the disease Methods and Results-When glycosuria is high (20 to 500 mg/dL), there is a selective reduction in the response to ␣ 1 and ␤ 2 agonists but not to dopamine or serotonin. When glycosuria is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
59
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 41 publications
(26 reference statements)
2
59
0
Order By: Relevance
“…47 Bovine aortic endothelial cells cultured in a high glucose environment, as well as aortas isolated from nonobese diabetic mice, exhibit increased caveolin-1 expression. 48 Hsp90 and caveolin-1 expression and their interactions with eNOS have been documented in the rat penis (Musicki et al, unpublished observations and references 14,49,50 ). The penis of the diabetic rat has been reported to contain decreased expression of caveolin-1 compared to that of the nondiabetic rat.…”
Section: Enos Expressionmentioning
confidence: 93%
“…47 Bovine aortic endothelial cells cultured in a high glucose environment, as well as aortas isolated from nonobese diabetic mice, exhibit increased caveolin-1 expression. 48 Hsp90 and caveolin-1 expression and their interactions with eNOS have been documented in the rat penis (Musicki et al, unpublished observations and references 14,49,50 ). The penis of the diabetic rat has been reported to contain decreased expression of caveolin-1 compared to that of the nondiabetic rat.…”
Section: Enos Expressionmentioning
confidence: 93%
“…In non-obese diabetic mice, modest hyperglycemia triggers s a selective reduction in the response to alpha1 and beta2 agonists but not to dopamine or serotonin (Bucci et al 2004). When glycosuria is severe (500 to 1000 mg/dl), there is a complete ablation vasoconstrictor responses to the alpha1 receptor agonist stimulation and a marked reduced response to beta2 agonist stimulation.…”
Section: Regulation Of No Production By Protein-protein Interactions mentioning
confidence: 99%
“…With increasing hyperglycemia, the authors found complete absence of contractile response to adrenergic signaling. However, normoglycemic NOD mice retained vascular reactivity similar to normal mice (CD-1) [22]. Normoglycemic NOD mice proceeded through pregnancy without complication, suggesting that in the disease-free state, neural, cardiovascular and endocrine adaptations are intact.…”
mentioning
confidence: 91%
“…This is supported by studies of overtly diabetic non-pregnant NOD mice that links hyperglycemia with vascular dysfunction [22]. Aortic rings from diabetic NOD mice have significantly impaired nitric oxide (NO)-dependent relaxation and vasoconstriction [22]. With increasing hyperglycemia, the authors found complete absence of contractile response to adrenergic signaling.…”
mentioning
confidence: 97%
See 1 more Smart Citation